Investigation of physical and mechanical properties of biocompatible coatings based on silver-hydroxyapatite deposited by radio-frequency magnetron sputtering; Перспективы развития фундаментальных наук - Syromotina D. S. (Физика, 2013)
Заглавие с экрана